Cyber Threat Extenuation for Substation Data Communication: Evaluation of Encrypt-Authenticator Prototype for IEC 60870-5 Data - Jidin R.; Jamil N.; Abdul Rahim A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Authentication; Field programmable gate arrays (FPGA); Authentication algorithm; Communication time; Data-communication; Electrical substations; FPGA implementations; Light-weight cryptography; Lightweight encryption; Programmable logic array; Cryptography